Platelet Aggregation Before Aspirin Initiation in Pediatric Patients With Congenital Heart Disease at High Risk of Thrombosis - Lu, Zhong-Yuan; Zhu, Zhi-Yuan; Yang, Ju-Xian; Zhou, Yu-Zi; Jiang, Ya-Zhou; Wei, Wei; Wang, Xu; Li, Shou-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background Aspirin following unfractionated heparin is the most common anticoagulation strategy for pediatric patients who experienced cardiac surgery at high risk of thrombosis. The platelet aggregation test is the golden method to evaluate the aspirin effect on platelet function. However, the platelet aggregation basal status before postoperative aspirin initiation and the related clinical influencing factors hasn't been investigated systemically in this population. Methods In a prospective cohort of 247 children, arachidonic acid-induced platelet aggregation (PAG-AA) was measured by means of light transmission aggregometry (LTA) before the first dose of aspirin after cardiac surgical procedure and the perioperative variables were also collected. Distribution of this population's PAG-AA basal status was described. Univariate and multivariate logistic regression analysis were performed to identify the main influencing factors of PAG-AA. Results The median time of aspirin administration was 2 (1–27) days after surgery and the corresponding median value of basal PAG-AA was 20.70% (1.28–86.49%), with 67.6% population under 55% and 47.8% population under 20%. Patients undergoing cardiopulmonary bypass (CPB) had a significantly lower basal PAG-AA than those without (30.63 ± 27.35 vs. 57.91 ± 27.58, p = 0.013). While patients whose test done within 3 days after CPB had a significantly lower PAG-AA than those out of 3 days (25.61 ± 25.59 vs. 48.59 ± 26.45, p = 0.001). Univariate analysis implied that the influencing factors of the basal PAG-AA including CPB use, test time point, cyanosis, and platelet count. Multivariate regression analysis indicated that only CPB use, test time point, and platelet count were the main independent influencing factors for the basal PAG-AA. Conclusion The majority of children have impaired basal platelet aggregometry responses before postoperative aspirin initiation. The main influencing factors are CPB use, test time point, and platelet count. To establish the platelet aggregometry baseline prior to commencement of aspirin therapy, testing should be performed 3 days later following the procedure when effect of CPB is basically over.